Anti-abrasive nanocoatings : current and future applications - Aliofkhazraei, Mahmood (Woodhead Publishing in materials., 2015)
This book provides an overview of the fabrication methods for anti-abrasive nanocoatings. The connections among fabrication parameters, the characteristics of nanocoatings and the resulting properties (i.e. nanohardness, toughness, wear rate, load-bearing ability, friction coefficient, and scratch resistance) are discussed. Size-affected mechanical properties of nanocoatings are examined, including their uses. Anti-abrasive nanocoatings, including metallic-, ceramic-, and polymeric-based layers, as well as different kinds of nanostructures, such as multi-layered nanocomposites and thin films, are reviewed. --